Evaluation of the Relationship between Oral Hygiene Index Simplified (OHI-S) and Oral Health Behavior - Moghaddami, Zeinab; Faezi, Mojgan; Semyari, Hassan (Galen Medical Journal, 2024)
Researchers aimed to explore oral health habits among medical students from diverse backgrounds. The primary focus was to understand the connection between the OHI-S index and oral health behaviors in Shahed University students in 2022. In this descriptive study, 175 participants from nursing, operating room, and dental programs were examined using the OHI-S index. Data collection involved demographic and oral health behavior questionnaires. Through simple random sampling, and after obtaining written consent, oral examinations were conducted. Researchers carefully assessed and recorded participants’ oral health status using the OHI-S criteria. The findings revealed interesting results: Dental students excelled in the plaque index, followed by nursing and operating room students. In terms of the calculus index, nursing students led, followed by dental and operating room students. Statistical analysis indicated a significant association between the field of study and the OHI-S index. Dental students achieved higher scores compared to their peers. Additionally, there was a notable relationship between gender and oral health behaviors, with females demonstrating better practices than males. In conclusion, the study highlights the impact of education on improving oral health habits. Dental students’ specialized knowledge contributed to their superior oral hygiene routines. These findings can be valuable in promoting oral health awareness among various medical student groups.